EDUBIMA BASED ON AUGMENTED REALITY: DEVELOPMENT OF DISASTER MITIGATION AND ENVIRONMENTAL MANAGEMENT LEARNING - Ratna Agustin; Nugroho Ari Wibowo; Gangga Kristin Nurfiyatul Jannah; Miranda Meifa; Muhammad Adam Yulloh (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This community service program aims to improve disaster preparedness and environmental management skills among students and educators at Muhammadiyah Boarding School (MBS) An-Nur Sidoarjo through the development of EDUBIMA learning media based on Augmented Reality (AR). The background for this activity is the high vulnerability of the Sidoarjo region to disasters and the low level of disaster knowledge and preparedness in the pesantren environment. The implementation methods include the development of AR learning media, interactive education, disaster response simulations, and evaluation using pre-tests and post-tests. The results showed a significant increase in disaster mitigation knowledge, from a low category of 56% to a high category of 70% after the intervention. This activity concludes that the use of AR-based EDUBIMA is effective in increasing disaster literacy and encouraging better environmental management behavior in the pesantren environment.